RANCANG BANGUN SISTEM KONTROL POMPA BENSIN ECERAN BERBASIS MIKROKONTROLER ATMEGA 32 - Teresna, I Wayan; Sumertayasa, I Made; Adi Purwadiyasa, Kadek (BULETIN FISIKA, 2016)
The development of science and technology are nowadays more and more provides ease of human life. Where all the things that a lot of applied science and technology with machinery or electronics, so that human work can be done easily without having to waste energy and shorten the time. Due to the many peoples who use manual way to sell gasoline with a bottle, then from this emerged an idea to create a means by which the tool can make it easier the way retail gasoline sales by using the system microcontroller atmega32, this tool almost followed the gasoline pump system contained in pertamina in general. In the gasoline level sensor, if the sensor has been reached which has been in the program the microcontroller, then the electric switch will work to open the tube above, after the sensor has reached the limit that has been in the program the microcontroller, then the flow switch will close again, after closing the flow switch then the pump will live and fill the tube back on.